Governing Chinese technologies: TikTok, foreign interference, and technological sovereignty - Ausma Bernot; Diarmuid Cooney-O'Donoghue; Monique Mann (Internet Policy Review, 2024)
TikTok bans have been presented as one solution to threats to national security, data security, foreign interference, child safety, and foreign espionage. In this article we investigate four countries/regions - Australia, the United Kingdom, the United States, and the European Union - that have banned or attempted to govern TikTok, examining the policy and legal bases for such restrictions. Our analysis is conceptually informed by legal and political narrations of foreign interference and technological sovereignty. We approach this with particular attention to countries with existing intelligence and data sharing agreements (i.e. three members of the Five Eyes alliance and the trilateral AUKUS alliance) and the European Union given its regulatory approach to data protection. This research makes significant and timely contributions to the geopolitics of TikTok and foreign interference in an international context. It informs inconsistencies in regulatory and legal approaches relating to foreign interference and data sovereignty, beyond "China threat" narratives. We argue that the European Union regulation presents an approach that attempts to protect citizens and citizen data rather than attack platforms and governments that challenge Western technological hegemony.
Keywords: 300; TikTok; Foreign interference; Digital sovereignty; Geopolitics; Surveillance